Anti-Trichophyton rubrum activity of the essential oil of Clinopodium brevicalyx and elaboration of a topical emulsion - Merma Ccana, Cinthya (2020)
Clinopodium brevicalyx grows in the southern high Andean regions of Peru and has wide popular use, however to date there is no research on its activity against Trichophyton rubrum, an anthropophilic dermatophyte fungus with an affinity for human keratin and difficult to treat, causing the most common superficial mycoses such as athlete's foot, ringworm and nail infections. The aim of this research was to determine the activity of the essential oil of Clinopodium brevicalyx against Trichophyton rubrum ATCC 28188. The essential oil was obtained by hydrodistillation, the extraction rate was 1.98 ± 0.02% (w/v), and the physicochemical characteristics were: relative density of 0.93654 g/mL, a refractive index of 1.4625, an optical rotation of 2.14°, and pH of 6.20. The chemical composition of the essential oil was determined using a gas chromatograph coupled to a mass spectrometer, identifying as main components: isomentone (44.24 %), menthone (22.22 %) and pulegone (8.23 %). The sensitivity of T. rubrum was evaluated by the disk diffusion method, establishing that at higher oil concentration more sensitivity of the fungus, the minimum inhibitory concentration of the oil was determined by the broth macro-dilution, obtaining a minimum inhibitory concentration (MIC) of 125 μL/mL. The topical emulsion with different percentages of essential oil, showed antifungal activity since 12.5% using the macrodilution method. Concluding that both the essential oil and the emulsion at 12.5% have antifungal activity against Trichophyton rubrum.